2016
DOI: 10.18632/oncotarget.7721
|View full text |Cite
|
Sign up to set email alerts
|

Control of CREB expression in tumors: from molecular mechanisms and signal transduction pathways to therapeutic target

Abstract: The cyclic AMP response element binding (CREB) protein has pleiotropic activities in physiologic processes. Due to its central position downstream of many growth signaling pathways CREB has the ability to influence cell survival, growth and differentiation of normal, but also of tumor cells suggesting an oncogenic potential of CREB. Indeed, increased CREB expression and activation is associated with tumor progression, chemotherapy resistance and reduced patients' survival. We summarize here the different cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 106 publications
3
108
0
1
Order By: Relevance
“…CRE B induced the robust expression of miR-132 in U87 cell lines. Previous studies reported that CRE B is an oncogene, which is related to tumor progression and patients' survival [39]. The CREB-miR-132 signaling pathway remains worthy of further study.…”
Section: Discussionmentioning
confidence: 92%
“…CRE B induced the robust expression of miR-132 in U87 cell lines. Previous studies reported that CRE B is an oncogene, which is related to tumor progression and patients' survival [39]. The CREB-miR-132 signaling pathway remains worthy of further study.…”
Section: Discussionmentioning
confidence: 92%
“…Although the detailed mechanisms of CnP remain unclear, a previous report showed that CnP inhibits cAMP‐responsive element binding protein (CREB) activation . CREB is a crucial transcription factor, which regulates a wide range of biological processes to orchestrate proper cell differentiation and cell growth . Moreover, CREB has previously been shown to regulate inflammatory responses by directly regulating gene transcription of proinflammatory genes, such as IL‐6 and TNF‐α, and CREB silencing has been shown to reduce the levels of IL‐6, IL‐8, and CCL2 in malignant mesothelioma cells .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is urgent to find new therapeutic targets. CREB belongs to basic/leucine zipper (bZIP) transcription factor family (22) and is described as a proto-oncogene (6,23). CREB play an important role at early stage of papilloma formation (24), promoted abnormal proliferation of myeloid cells in vitro and in vivo and was implicated in myeloid cell transformation (6).…”
Section: Discussionmentioning
confidence: 99%